Incorporating Social Workers and Nurses to Provide Hospice Patient’s with an Effective Quality of Life - Carpenter-Aeby, Tracy; Aeby, Victor; Brown, LaNeisha; Collins-Best, Vickie; Heath, Samantha; Keyes, Jocelyn (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Ensuring quality of life for hospice patients requires attention to spiritual, financial, andpsychosocial needs which is largely the focus of hospice care professionals. Providing quality oflife to patients in hospice requires addressing those needs which cannot be accomplished alone butmost effectively as part of an interdisciplinary team. This systematic literature review will explorethe effectiveness of social workers and nurses who work on an interdisciplinary team in regards toproviding quality of life to hospice patients. Through the review of literature this paper will seekto support the hypothesis that interdisciplinary teams between social workers and nurses canincrease the quality of life for patients who receive hospice services. The purpose of this study is to determine what professionals can work together and are most effective as an interdisciplinaryteam to provide quality of life for hospice patients.